2018
DOI: 10.1093/nar/gky1282
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of RNA polymerase III genes during liver regeneration

Abstract: Mouse liver regeneration after partial hepatectomy involves cells in the remaining tissue synchronously entering the cell division cycle. We have used this system and H3K4me3, Pol II and Pol III profiling to characterize adaptations in Pol III transcription. Our results broadly define a class of genes close to H3K4me3 and Pol II peaks, whose Pol III occupancy is high and stable, and another class, distant from Pol II peaks, whose Pol III occupancy strongly increases after partial hepatectomy. Pol III regulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 35 publications
4
15
0
Order By: Relevance
“…We found that pol III occupancy in the liver of WT mice decreases during the fed to fasted transition but this response is limited to mostly low and intermediate occupancy genes; high occupancy genes are essentially unchanged. Similar findings involving overlapping subsets of stable and changing genes are seen following a partial hepatectomy 18 . In contrast, in Maf1 -/mice, pol III occupancy was increased for the majority of active loci in liver, regardless of their occupancy level, and the levels of specific precursor tRNAs in this tissue and in other organs are higher than wild-type in both fed and fasted conditions.…”
Section: Introductionsupporting
confidence: 62%
See 2 more Smart Citations
“…We found that pol III occupancy in the liver of WT mice decreases during the fed to fasted transition but this response is limited to mostly low and intermediate occupancy genes; high occupancy genes are essentially unchanged. Similar findings involving overlapping subsets of stable and changing genes are seen following a partial hepatectomy 18 . In contrast, in Maf1 -/mice, pol III occupancy was increased for the majority of active loci in liver, regardless of their occupancy level, and the levels of specific precursor tRNAs in this tissue and in other organs are higher than wild-type in both fed and fasted conditions.…”
Section: Introductionsupporting
confidence: 62%
“…(i) Of the 212 high occupancy genes in the PH dataset (average occupancy score > 3.5, see Table S4 in ref 18 ), 197 were not significantly changed by PH. Of these, 90% (177 genes) were also not significantly changed upon fasting ( Figure 1C, black dots).…”
Section: Fasting and Refeeding Affects Pol III Occupancy In Mouse Livermentioning
confidence: 99%
See 1 more Smart Citation
“…Pol III transcription is regulated in different biological processes such as the cell cycle (White et al 1995), differentiation (Alla and Cairns 2014;Van Bortle et al 2017), development (Schmitt et al 2014), regeneration (Yeganeh et al 2019), and cellular stress (Upadhya et al 2002). Its activity is controlled by MAF1, a protein conserved from yeast to human that binds to the enzyme and represses its activity, and by a number of tumor suppressors and oncogene products that act on Pol III transcription factors (for review, see Marshall and White 2008;Gjidoda and Henry 2013).…”
mentioning
confidence: 99%
“…However, based on differential binding of RNAPIII, many studies have revealed that tRNA genes are not equally transcribed in mammalian cells, as measured by the differential binding of RNAPIII (7-9). Genome-wide studies examining chromatin accessibility, modification and transcription factor binding have suggested that a driver of RNAPIII occupancy at tRNA genes is open and active chromatin, typically in the vicinity of RNAPII transcription sites, yet the basis for differential RNAPIII binding remains to be determined (7,8,49,50). Further studies are needed to assess how host chromatin accessibility and modifications change during MHV68 infection.…”
Section: Discussionmentioning
confidence: 99%